2015
DOI: 10.1007/s00586-015-3968-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of combined anterior–posterior approach versus posterior-only approach in treating adolescent idiopathic scoliosis: a meta-analysis

Abstract: Posterior-only approach can achieve similar coronal plane correction and percent-predicted FEV1 compared to combined anterior-posterior approach. The posterior approach even does better in sagittal correction in severe AIS patients. Significantly less complication rate, blood loss, operative time, length of hospital stay and better percent-predicted FVC are also achieved by posterior-only approach. Posterior-only approach seems to be effective and safe in treating AIS for experienced surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 30 publications
0
32
1
3
Order By: Relevance
“…20 Nevertheless, newer techniques have allowed for similar results in terms of degree of correction and outcomes for posterior-only approaches, with less postoperative morbidity, lower blood loss, and shorter stay. 5 Though construct length 29 and osteotomy 6,21 have been associated with higher rates of adverse events in corrective surgery for adult scoliosis, we found no evidence of these associations for the AIS patients in the present study. Daubs et al noted that once the fusion length reaches 5 or more levels in adult spinal deformity, the addition of more segments may not necessarily increase complication rates, 8 and since AIS patients generally have more than 5 levels fused, it is possible that Daubs et al's finding also applies to the AIS population.…”
Section: Discussioncontrasting
confidence: 73%
“…20 Nevertheless, newer techniques have allowed for similar results in terms of degree of correction and outcomes for posterior-only approaches, with less postoperative morbidity, lower blood loss, and shorter stay. 5 Though construct length 29 and osteotomy 6,21 have been associated with higher rates of adverse events in corrective surgery for adult scoliosis, we found no evidence of these associations for the AIS patients in the present study. Daubs et al noted that once the fusion length reaches 5 or more levels in adult spinal deformity, the addition of more segments may not necessarily increase complication rates, 8 and since AIS patients generally have more than 5 levels fused, it is possible that Daubs et al's finding also applies to the AIS population.…”
Section: Discussioncontrasting
confidence: 73%
“…15 There are, however, disadvantages of combined anterior release, including the learning curve for the surgeon, cardiopulmonary compromise, adjacent-organ injuries, increased hospital stay and cost, halo traction complications before posterior procedures, and having the anesthesia risks of 2 major operations. 14,16 The main problem of the combined anterior and posterior procedure is the risk of pulmonary complica-tions. 6,17,18 Some studies have used preoperative traction or traction between 2 stages of surgery as a part of correction.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no reported differences in blood loss, length of hospital stay and patient reported outcomes between both approaches, the posterior approach may save on the negative impacts of the anterior approach on pulmonary function. Studies also showed that the posterior-only approach has the same correction as a combined anterior/posterior spinal fusion, without the need for entering the thorax and thus negatively impacting pulmonary function [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Surgical Managementmentioning
confidence: 99%